Countering Islamophobia in Portugal: experience of Indonesian Muslim expatriates - Sa'adi Sa'adi (Indonesian Journal of Islam and Muslim Societies, 2021)
The main purpose of this research is to investigate the Indonesian Muslim expatriate experiences in countering Islamophobia in Portugal. There are 488 Indonesian expatriates in Portugal, of whom 384 (78%) are Muslims, working on diplomatic missions, students, traders, professionals, laborers, and others. To analyze the data, the researcher used triangulation techniques such as interviews through guided written questions, observation, and documentation, using factor analyses covering items of Portugal government policy on religious life, characters of Portuguese culture, the characters of Indonesian Muslim socio-culture, educational background of Indonesian Muslim expatriates, and normative Islamic teaching inspiring their socioreligious views and attitude. As the main findings, the research revealed that in countering the Islamophobia experience, the Indonesian Muslim expatriates in Portugal feel joy, safety, peace, a harmonious life. Also, they feel like in their home towns; they can access public services easily and practice private, and religious activities normally, although the number of mosques in public places is very few. None of them experienced extreme hatred, prejudice, harassment, hostility, bad words, bad attitudes and treatments, discrimination, and Islamophobia from local citizens or other groups.